BANINE ET KURBAN SAID: TRIBULATIONS DEPUIS BAKOU JUSQU'À L'EUROPE («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article talks about the amazing fate and literary career of two writers who were born at the beginning of the 20th century in Baku into families of wealthy oil industrialists belonging to different cultures. These two Baku residents, destined by birth for an idle, carefree life, by the will of historical events lived a life that was not at all intended for them... And the spirit of the city in which they were born, grew up, spent their youth, helped them survive in the whirlwind of historical events of the first half of the 20th century, in incredibly difficult conditions of emigration in Europe, and not only survive, but also become famous: Banin and Kurban Said
Keywords: Baku, Silk Road, Caucasus, Cosmopolitanism, 20th century, Banin, Caucasian days, I chose... Opium, Catholicism, Kurban Said, Ali and Nino, Islam, oil tycoons